Respostas
respondido por:
1
x²/2 - x - 24 = 0⇒
x² - 2x - 48 = 0⇒
2
x² - 2x - 48 = 0⇒
x1 = 2 + √(-2)² - 4.1. (-48)⇒
2.1
x1 = 2 + √196⇒
2
x1 = 2 + 14⇒
2
x1 = 8
x2 = 2 - 14⇒
2
x2 = - 12⇒
2
x2 = - 6
V {-6, 8}
Espero tê-lo ajudado
Bons Estudos
kélémen
x² - 2x - 48 = 0⇒
2
x² - 2x - 48 = 0⇒
x1 = 2 + √(-2)² - 4.1. (-48)⇒
2.1
x1 = 2 + √196⇒
2
x1 = 2 + 14⇒
2
x1 = 8
x2 = 2 - 14⇒
2
x2 = - 12⇒
2
x2 = - 6
V {-6, 8}
Espero tê-lo ajudado
Bons Estudos
kélémen
kelemen1:
Obrigado pela sua avaliação. kélémen
Perguntas similares
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás